Identification of key research needs for topical therapy treatment of psoriasis – a consensus paper by the International Psoriasis Council. (10th March 2016) - Wu, J.J.; Lynde, C.W.; Kleyn, C.E.; Iversen, L.; van der Walt, J.M; Carvalho, A.; Kirby, B.; Bissonnette, R.
Abstract: In this age of expanding choices of therapy for psoriasis, topical therapies still play an important part in the management of patients. There are many knowledge gaps in topical therapy for psoriasis with regard to efficacy and safety as well as various combinations including topical therapy with phototherapy or with systemic agents. Councillors of the International Psoriasis Council comprised a topical therapy working group to describe these gaps in order to help direct future research endeavours. Herein, we present the results of this analysis, discuss topical agents in clinical development and the attributes of the ideal topical treatment for psoriasis.